Estudo da composição , frequência de ocorrência e abundância relativa das algas epilíticas de corredeiras do médio rio Xingú (Pará, Brasil) - GUIMARÃES, Robledo Hideki Ebata (2019)
The epilithon is one of the most important communities in shallow water environments, because their active participation in the metabolism of freshwater ecosystems and the primary productivity. They are excellent bioindicators of water quality and its trophic state due to the fact that their species make a short life cycle and accumulate nutrients, pollutants such as insecticides, herbicides, fungicides and heavy metals. The aim of this study was to characterize the community structure of epilithic algae in the Middle Rio Xingu (Pará, Brazil). To achieve this was carried out in environments of rapids in the study sites of Boa Esperança (BE), and 03o34'46''S 52o24'42''W, and Arroz Cru (AC), and 03o33'47''S 51o24'40''W. Samples were taken in periods of low rainfall (August and September 2006) and the period of greatest rainfall (February and March 2007). Samples were obtained by scraping a known area of rock chosen randomly. All material was fixed in Transeau solution. A total of 100 species of epilithic algae were identified during the study period. Diatoms were dominant in qualitatively different seasonal periods, followed by green algae (Chlorophyta and Charophyta), cyanobacteria and Euglenid. The species Aulacoseira granulate (Ehrenberg) Simonsen and Oedogonium sp.1 Link were very common, occurring in more than 70% of samples, since the other species were classified as sporadic (42.52%), uncommon (36.63%) and common (18.81%). The most abundant species were classified as Oedogonium sp.1 Link abundant and low abundant in Good Hope and paddy, respectively, in the month of september. Aulacoseira granulate (Ehrenberg) Simonsen and Eunotia flexuosa (Brébisson) Kützing as little abundant in Boa Esperança, in the month of February and Oscillatoria sp.1 Vaucher ex Gomont, Mougeotia delicata as little abundant in Arroz Cru in the month of February.